The Extracellular Matrix Protein ABI3BP in Cardiovascular Health and Disease - Delfín, Dawn A.; DeAguero, Joshua L.; McKown, Elizabeth N. (Frontiers in Cardiovascular Medicine, 2019)
ABI3BP is a relatively newly identified protein whose general biological functions are not yet fully defined. It is implicated in promoting cellular senescence and cell-extracellular matrix interactions, both of which are of vital importance in the cardiovascular system. ABI3BP has been shown in multiple studies to be expressed in the heart and vasculature, and to have a role in normal cardiovascular function and disease. However, its precise role in the cardiovascular system is not known. Because ABI3BP is present in the cardiovascular system and is altered in cardiovascular disease states, further investigation into ABI3BP’s biological and biochemical importance in cardiovascular health and disease is warranted.